WHITE SHOES & THE COUPLES COMPANY SEBAGAI AKTOR DIPLOMASI BUDAYA INDONESIA DALAM BERBAGAI FESTIVAL MUSIK INTERNASIONAL (PERIODE 2008-2013) - Salim Lubis, (2022)
Cultural Studies is one of the most rapidly growing branch in the science of international relations, especially after the end of World War II. One of the concepts of postcolonialism that emerged as a real impact of the development of this study is the concept of cultural hybridization. This concept tends to be very close to third world countries which are mostly influenced by colonialism. However, this concept continues to develop and is also applied in various purposes, including the cultural diplomacy agenda. White Shoes & The Couples Company is a band from Indonesia which also applies the concept of cultural hybridization musically in their works. The adaptation of this concept as an effort to redefine and interpret the sound of Indonesian music later helped them represent Indonesia in various international music festivals, especially in the period of 2008-2013. This study uses a descriptive qualitative method to describe how the concept of cultural hybridization is applied through the effort of defining the "Indonesian" values and identity through the works of White Shoes & The Couples Company. In addition, their journey as Indonesian cultural diplomacy actors through various international music festivals for the period 2008-2013 will also be explained, along with the further details about various aspects that support the agenda. Keywords: White Shoes & The Couples Company, Cultural Hybridization, Cultural Diplomacy.